Rancang Bangun Sistem Informasi Pembelian Dan Penjualan Berbasis Web Pada CV. D’gung Collection - Ni Kadek Sucitrawati; A.A. Istri Ita Paramitha; Ni Made Estiyanti (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2022)
This study aims to determine the suitability of the buying and selling system applied in CV. D'Gung Collection. The research method used in this study is the waterfall method, namely the method by means of interviews to collect data as a determinant of the success of a study. In the process of working on the design of this buying and selling system using the PHP programming language and the Laravel framework. The WEB-based buying and selling system that has been designed has been successfully implemented so that it can help the buying and selling process that is carried out every day on CV. D'Gung Collection well.